Design and Implementation of Functional Drink Product Inventory Applications at Kulon Progo MSMEs - Munambar, Siwitri Munambar; Annisa Wirrdiana Yuniasih; Prayoga, Adi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
The importance of the innovation process and the novelty of the MSME system is one of adding value to MSMEs in the current globalization. One of the innovation processes that need to be carried out is to improve the digitization process of MSMEs. Kulon Progo MSMEs do not have accurate and efficient inventory records, which is one of the causes of inventory management that has not been managed optimally. Based on the problems that occur in Kulon Progo MSMEs, it is necessary to develop a digital-based inventory application in order to minimize product recording errors. Therefore, this study aims to apply digital-based inventory applications to functional beverage products in Kulon Progo MSMEs. This research was conducted in January-June 2024 at one of the MSMEs located in Kulon Progo Regency, Yogyakarta Special Region. The data collection method used uses interviews, observations, and literature studies. While the application development method uses the Waterfall method. the use of AppSheet-based inventory applications in Kulon Progo MSMEs can be implemented properly. After passing the implementation and testing stages, the application can be applied to manage inventory by recording product entry and exit. The application of mixed functional beverage product inventory applications in Kulon Progo MSMEs simplifies the recording process for MSMEs and can be a solution to inventory problems in MSMEs.